The Role of Religion in Eastern Europe Today - Gerlach, Julia (Springer, 2015)
​While religion was expelled from the public space during Communist times and became a secret form of “inner emigration”, it entered the empty public space again in Post-Communist times. Public interest in religious issues and the public prestige of religion have dramatically increased. The book “Under Construction. The Role of Religion in Eastern Europe Today” deals with the (re-)emergence of religion in Eastern Europe and its impact on the economy, the society, and the state in 15 essays. The authors represent various fields of science related to human interaction – Economics, Political Science, Sociology, and Law. The added value is an up-to-date and interdisciplinary perspective on religion and its effects in major spheres of the societies in Eastern Europe today.